1980
DOI: 10.1111/j.1432-1033.1980.tb04725.x
|View full text |Cite
|
Sign up to set email alerts
|

Xylan‐Degrading Enzymes of the Yeast Cryptococcus albidus

Abstract: During growth on wood β‐1,4‐xylans the yeast Cryptococcus albidus produced at least two enzymes which convert the polysaccharide to xylose catabolized by the cells. The enzyme almost completely secreted into culture fluid was identified as an endo‐1,4‐β‐xylanase.The function of the extracellular β‐xylanase is to hydrolyze xylan to oligosaccharides, mainly to xylobiose and xylotriose, which enter the cell where they are split by the second identified enzyme, a cell‐bound β‐xylosidase (xylobiase). Aryl β‐xylosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(50 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…Activities of the various enzyme preparations on 0.15 mg of p-nitrophenyl ␤-D-glucopyranoside (4-NPG; Sigma) were assayed in 0.3 ml of 0.05 M sodium acetate, pH 5.2, at 30°C. The reaction was terminated by the addition of 0.6 ml of 4% (w/v) Na 2 CO 3 (16), and the absorbance of the reaction mixture was read at 410 nm with a spectrophotometer.…”
Section: Extraction Of a Coat Fraction By Diethyl Ether From Pollen Amentioning
confidence: 99%
“…Activities of the various enzyme preparations on 0.15 mg of p-nitrophenyl ␤-D-glucopyranoside (4-NPG; Sigma) were assayed in 0.3 ml of 0.05 M sodium acetate, pH 5.2, at 30°C. The reaction was terminated by the addition of 0.6 ml of 4% (w/v) Na 2 CO 3 (16), and the absorbance of the reaction mixture was read at 410 nm with a spectrophotometer.…”
Section: Extraction Of a Coat Fraction By Diethyl Ether From Pollen Amentioning
confidence: 99%
“…The xylanases were assayed according to Biely et al (1980) with a few modifications, as suggested by Lara et al (2014). The reducing sugars released were determined using the dinitrosalicylic acid method, i.e.…”
Section: Determination Of Xylanase Activitymentioning
confidence: 99%
“…It will certainly be of interest to examine isomeric xylooligosaccharides for ability to induce the xylan-degrading enzyme system of the studied yeast because they undergo much slower enzymic degradation than the best natural inducers, 1,4-P-xylobiose and 1,4-P-xyIotriose [31]. There are several examples in the literature of effective induction of glycanases by positional isomers of natural oligosaccharide substrates and products [32-371. …”
Section: Furc~ioti 111mentioning
confidence: 99%
“…The specificity could result from the fact that the binding sites of these enzymes consist of several subsites displaced on both sides from the catalytic groups [lo, 131. We expected that this was also true for endo-I ,4-p-xylanase of Cryptococcus albidus catalyzing transfer reactions at high concentrations of 1,4-8-xylooligosaccharides or aryl p-xylosides [14,15]. However, during chromatographic isolation of the main transfer products of phenyl [h-xylopyranoside degradation, identified as 1,4-~-xylooligosaccharides, we observed that the reaction mixture also contained small amount of xylooligosaccharides different from the 1,4-fi-linked products [16].…”
mentioning
confidence: 99%